Business improvement districts (BIDs): An economic development policy or a tool for gentrification - Bakry Elmedni; Nicole Christian; Crystal Stone (Cogent Business & Management, 2018)
This paper examines the roles of business improvement districts (BIDs) in revitalizing struggling neighborhoods and downtown areas in urban settings. For decades, New York City has been using BIDs as policy tool to help businesses thrive in rough areas. Previous research has shown that while BIDs can be very useful tool for enhancing the physical appearance, bringing in more foot traffic and increasing the property value in the districts where are instituted, they can also be a driver for complete transformation of a neighborhood by raising the real estate value. In doing so, they increase residential and commercial rental rates in the area. In addition to revitalizing dilapidated areas, BIDs can also be counterproductive by shifting the burden to low-income residents and small business owners. This paper outlines and documents the process through which BIDs transform an area from the perspectives of renters, business owners and BIDs directors in 16 of Brooklyn's 25 BIDs districts. Using qualitative research design, we interviewed 46 participants in these districts, including 16 BIDs directors. The study shows in the process of transforming an area that BIDs produce immediate, intermediate, long-term and lasting impacts. Immediate impacts range from enhancing the physical appearance to increase in sales while intermediate and lasting impacts range from driving rental rates to complete social and cultural transformation of the area in few years.
Keywords: 650